Diving deeper into the taxonomy of the Neoscopelus species complex (Myctophiformes: Neoscopelidae) with the description of Neoscopelus serranoi sp. nov. - Bañón, Rafael; Barros-García, David; Arronte, Juan Carlos; Rábade, Sonia; Rio, José Luis Del; Baldó, Francisco; Carlos, Alejandro De (Zootaxa, 2024)
Previous studies have highlighted possible cryptic biodiversity in the genus Neoscopelus. This hypothesis was tested using new morphological, molecular and biogeographical data on species of this genus caught in the north Atlantic between 2010 and 2022. The information obtained has been combined with available data in an integrative approach, including a review of morphological characters reported in the ichthyological literature and DNA-based species delimitation analyses. The main outcome of the present study is the description of Neoscopelus serranoi sp. nov. from the Atlantic and southwestern Indian Oceans. The new species is morphologically very similar to Neoscopelus microchir from which differs in having a shorter anal-fin base, a shorter pelvic fin, more dorsal and pectoral-fin rays, less anal-fin rays, fewer gillrakers and fewer isthmus and lateral photophores. They also differ in geographic distribution, with the new species occurring in the Atlantic Ocean and the near southwestern Indian Ocean, whereas N. microchir was originally described from Japanese waters of the Pacific Ocean. A literature review of available morphological data between geographic areas for Neoscopelus macrolepidotus and Neoscopelus microchir showed a large intraspecific overlap and no boundaries. However, molecular species delimitation based on the mitochondrial COI gene revealed the existence of cryptic diversity in both species, with eight to ten molecular operational taxonomic units (MOTU), compared to three valid species. Neoscopelus serranoi sp. nov. was considered an independent MOTU in all analyses performed, supporting the morphological identification as a new species. These results highlight that the taxonomy of Neoscopelus is far from settled and show that a greater sampling effort is needed to resolve the uncertainties and to describe unknown putative species. This also exemplifies the virtues of integrative taxonomy in delving into the systematics of deep-sea fishes.